Regular expressions for beginners and beyond. (Manning Publications, 2022)
Regular expressions have a bad reputation for being difficult to understand. This course introduces tools and a systematic approach so you can unlock the power of regular expressions to write compact, elegant code. In this course, we will cover concepts from basic to advanced. The examples progress in a logical, narrative way. At the end of one example, we will think about how we might tweak it to do something similar but more powerful. In this way, the concepts flow naturally from one example to the next. There are also 41 exercises. You are given a description of a regular expression, and then you write it using your choice of JavaScript or Python syntax. After you're done, tests written especially for the exercises will let you know whether your regular expressions did the job they were supposed to. These exercises are a fun, interactive way to cement the concepts in your brain, and make sure you really understand the material presented in the lectures. Depending on your level of experience, you can start at the beginning, or start later with concepts you've always been interested in, but haven't had a chance to learn yet.